Peralihan Hak Atas Tanah bagi Pegawai Negeri yang Ingin Memiliki Rumah Dinas dari Pemerintah - Parmono Bikan (Al-Qanun: Jurnal Pemikiran dan Pembaharuan Hukum Islam, 2017)
In order to improve the welfare of public servants, the Government provides official housing, which of them can be owned by leasing. The payments are through the withholding of the civil servant's salary each month, and a lease agreement is made in the presence of a Notary Public. After the expiration of the lease period, the Government issues Letter of Release of Rights to the civil servant made before the Notary. The conclusion of this writing is: first, the authenticity of the deed of sale and purchase of government land purchased by Public Servant is valid and has perfect proof power, but in the case for the handling of ownership in the Land Office, the deed of sale and sale can not be used as the requirements, but the Deed or Letter of Release of Rights of the government made before the Notary. Secondly, the legal protection for Civil Servants who buy a State house for residence is a regulation through legislation, consisting of arrangements concerning the procedure of granting property rights to a civil servant or his heirs of the official housing he buys.